Aware, motivated and striving for a 'safe tan': an exploratory mixed-method study of sun-protection during holidays. Issue 1 (1st January 2017) - Rodrigues, Angela M.; Sniehotta, Falko F.; Birch-Machin, Mark A.; Araujo-Soares, Vera
ABSTRACT: Background: This article presents an exploratory study, aiming to explore the correspondence between knowledge, motivation and sun-protection practices during holidays. Methods: Seventeen participants aged 21–62 years old, recruited from community settings took part in individual face-to-face semi-structured interviews, completed sun sensitivity questions and an objective assessment of sunscreen use. Holidaymakers' knowledge about sun-safe messages, intentions and perceptions of barriers and facilitators for sun-protection were assessed. Qualitative data were analysed using thematic analysis and integrated with quantitative data, using a pragmatic theory-informed approach to synthesise the findings. Results: Participants were well informed about sun-safe messages, highly motivated to protect themselves from solar UV radiation (UVR) and they perceived themselves as well protected. However, they did not seem to use effective protective practices. Sunscreen was the preferred method of sun-protection, but most participants used considerably less than the recommended amount and significantly overestimated the amount of time they could be safely exposed. Seeking shade was the least used method of sun-protection and covering-up strategies were mostly implemented as a partial protection (i.e. hats or sunglasses). The desire to reach an optimal balance between getting a tan and using sun-protection to avoid sunburns was preeminent. Several additional barriers and facilitators for sun-protection were identified. Conclusions: Holidaymakers might have a false sense of security when it comes to sun-exposure. They are aware of the need to protect from solar UVR, but the motive for a safe tan, the overreliance on sunscreen, the overestimation of the safe sun-exposure time for their skin type and the insufficient application of sunscreen leaves holidaymakers motivated to protect their skin at significant risk of overexposure, sunburn and skin cancer. Public health messages need to address how to implement effective sun-safe strategies.